1985
DOI: 10.1038/clpt.1985.65
|View full text |Cite
|
Sign up to set email alerts
|

High levels of methylxanthines in chocolate do not alter theobromine disposition

Abstract: Theobromine disposition was measured twice in 12 normal men, once after 14 days of abstention from all methylxanthines and once after 1 week of theobromine (6 mg/kg/day) in the form of dark chocolate. Mean theobromine t 1/2, apparent volume of distribution, and clearance after abstinence from all methylxanthines were 10.0 hours, 0.76 L/kg, and 0.88 ml/min/kg. High daily doses of chocolate for 1 week did not change these values. After subjects abstained from methylxanthines, urinary radioactivity over 72 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 9 publications
0
16
2
Order By: Relevance
“…This is in line with the fact that paraxanthine is slightly more potent than caffeine in antagonising the effects of adenosine. 29 Although theobromine has also been shown to increase natriuresis and to present similar properties than other methylxanthines, 21 we found no significant association of theobromine with BP. Theobromine has one fifth the stimulant effect of caffeine, and acute theobromine and caffeine intake have previously been shown to exert opposite results on BP among 24 healthy female volunteers.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This is in line with the fact that paraxanthine is slightly more potent than caffeine in antagonising the effects of adenosine. 29 Although theobromine has also been shown to increase natriuresis and to present similar properties than other methylxanthines, 21 we found no significant association of theobromine with BP. Theobromine has one fifth the stimulant effect of caffeine, and acute theobromine and caffeine intake have previously been shown to exert opposite results on BP among 24 healthy female volunteers.…”
Section: Discussioncontrasting
confidence: 52%
“…Other methylxanthine-related mechanisms possibly involved include sympathomimetic effects, smooth muscle relaxation, and phosphodiesterase inhibition. 20,21 We found no consistent association of 24-hour caffeine and caffeine metabolite excretions with DBP. Although the reason of the differential associations of caffeine and caffeine metabolites on SBP and DBP is not entirely clear, it is compatible with the hypothesis that methylxanthines influence BP via their natriuretic property.…”
Section: Discussioncontrasting
confidence: 41%
“…Clinical investigations with mammals have shown that theobromine exerts diverse pharmacological effects (diuresis, stimulation of the cardiovascular system and glandular secretions) and relaxation of the growth muscles (Shively et al, 1985) while studies with poultry and pigs have recorded pancreatic and liver enlargements (Braude and Foot, 1942;Odunsi and Longe, 1995a) and increased mortality. Theobromine intake was calculated to be 12·8 g/d for chicks fed on the 300 g/kg UCBC diet while the chicks fed on the corresponding WCBC and ACBC diets ingested 5·95 and 4·45 g/d.…”
Section: Growth and Nutrient Retentionmentioning
confidence: 98%
“…However, there is no information relating to the pharmacokinetics of PX in man although some studies of TB pharmacokinetics and metabolism in humans have been reported Drouillard et al, 1978;Miners et al, 1982Miners et al, , 1985Shively et al, 1985;Simons et al, 1984;Tarka et al, 1983 Protocol Equimolar oral doses of TP, TB, PX (250 mg of each) and CA (270 mg) were separately administered to each subject. Subjects fasted from the evening prior to and until 4 h following methylxanthine administration on each study day.…”
Section: Introductionmentioning
confidence: 99%